Por uma escuta transgressora: discursividades praticadas por mulheres transexuais, por mulheres transgêneras e por travestis ao falarem sobre si - Moura, João Vítor Sampaio de (2022)
This research aimed to analyze the discursivities produced by transsexual women, transgender women and travestis when talking about themselves, linking to the studies in Applied Linguistics that has the body as a theme. In terms of specific objectives, it was concerned to: a) understand, through representations of/in the discourse, how the research participants discursively objectify their bodies and how they feel and/or mention that they have them objectified by the other; b) investigate the participants' own discursive strategies of constructing identification as a transsexual woman, a transgender woman, and a travesti; c) identify ways, strategies and/or discourses of resistance practiced by them. For this, previous works on the topic of language and transsexual women, transgender women and travestis were reviewed, as well as the data collection and analysis, in the discursive scope, of some testimonials. Moreover, it should be noted that, in this paper, we discuss the issue of the body as an object of study in/by language; to this end, a distinction is made between the biological body and the body of language, with the last one being a social construction that is built on performance. For this reason, the idea of gender and sexuality is discussed, demonstrating that gender, as a social construction, is the result of a historical and political process. Further, we discuss FrancoBrazilian discourse analysis, in which some of the most prominent characteristics of this school are pointed out, determining its relationship with Applied Linguistics. Finally, the present work is placed within the context of decolonial studies, especially its feminist variant. We should also highlight the importance of transgressive listening as a way to get closer to the participants’ universe, since it is a political approach that attempts to place the analysis of their discourse in a context of resistance. The theoretical-methodological apparatus is constituted by studies in Applied Linguistics (HASHIGUTI, 2008; PENNYCOOK, 2006; MOITA LOPES, 2006), Discourse Analysis (PÊCHEUX, 1997), decolonial studies (MIGNOLO, 2018; MALDONADO TORRES, 2016) and decolonial feminism (VÈRGES, 2019; CURIEL, 2019). The present work makes use of the AREDA Proposal (Analysis of Discursive Resonances in Open Statements), which brings together Discourse Analysis and Psychoanalysis in an interdisciplinary proposal. Thus, in accordance with the proposal, we should be aware of the interpretative gestures and the development of an analytical device. The analysis was conducted in a way that the theoretical-methodological apparatus was in dialogue with the precepts of the AREDA proposal (SERRANI-INFANTE, 1998), in particular with regard to the enunciative regularities present in the participants' speeches. Through these regularities, it was possible to identify representations of the themes that predominated in their speeches. As results, we emphasize the presence of meanings regarding the coloniality of knowledge, being, and power in terms of how their bodies are often named/looked upon and how, at the same time, they act as the possible forms of transgression and inquiry about their life experiences.